2018
DOI: 10.3171/2016.9.jns16622
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-orbitozygomatic approach: functional and cosmetic outcomes in a series of 169 patients

Abstract: OBJECTIVE Advantages of the fronto-orbitozygomatic (FOZ) approach have been reported extensively in the literature; nevertheless, restoration of normal anatomy and the esthetic impact of surgery are increasingly important issues for patients and neurosurgeons. The aim of this study was to analyze functional and cosmetic outcomes in a series of 169 patients with different pathologies who underwent surgery in which the FOZ approach was used. METHODS Between January 2000 and December 2014, 250 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…As neurosurgical techniques continue to evolve, secondary but important cosmetic outcomes have acquired an increasing focus in addition to surgical outcomes. 13,14 Therefore, an informed discussion with the patient is warranted, comparing the risks and benefits of each approach. In our series, we used the supraorbital approach in 20 patients with anterior skull base meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…As neurosurgical techniques continue to evolve, secondary but important cosmetic outcomes have acquired an increasing focus in addition to surgical outcomes. 13,14 Therefore, an informed discussion with the patient is warranted, comparing the risks and benefits of each approach. In our series, we used the supraorbital approach in 20 patients with anterior skull base meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that there can be negative cosmetic results related to the excessive mobilization of the temporal muscle, which is part of the transzygomatic subtemporal approach. In a series of 250 patients undergoing variations of the orbitozygomatic craniotomy, the following adverse cosmetic results have been noted: forehead hypesthesia in 41%, frontal weakness in 10%, and diplopia in 6% (Boari et al, ). Additionally, postoperative palsy of the frontal branches of the facial nerve can result in a poor cosmetic result.…”
Section: Discussionmentioning
confidence: 99%
“…Orbitotomy and the zygomatic resection of conventional approaches is a technically demanding procedure that requires time for their correct execution and repair [ 8 , 17 , 24 ]. Boari et al [ 3 ] reported that the mean time required for orbitotomy and orbital reconstruction was about half an hour in a fronto-OBZ approach. The technique that we propose has the advantage that, by not removing the orbit, its reconstruction is not necessary, in that a thin bony plate is preserved to contain the eyeball and the periorbital soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsatile enophthalmos or the development of exophthalmos has been one of the most recurrent and significant complications associated with lateral and superior orbital wall removal from the OBZ approach [ 3 , 9 , 11 , 12 , 19 ]. Even in conventional approaches, it is argued that it is necessary to respect at least one-third of the orbital roof and to carry out an excellent anatomical reconstruction to avoid modifications in eyeball position [ 6 , 19 , 20 , 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%